The relationship of perceived value on purchase intention towards sportswear among FSR student UiTM Seremban / Nurliyana Ahmad Rasdin and Mohammad Adzly Rajli - Ahmad Rasdin, Nurliyana; Rajli, Mohammad Adzly (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The study explores how perceived value affects sportswear purchase intention among Faculty of Sports Science and Recreation (FSR) students at Universiti Teknologi MARA (UiTM) Seremban, focusing on gender differences and their impact on consumer behavior. Existing literature highlights unclear relationships between gender [1] and purchase intention and the limited exploration of perceived value’s role in purchase intention, creating a need for this research [2]. This quantitative study utilized a survey method with a questionnaire distributed to 362 FSR students selected through probability sampling. Data were analyzed using Jamovi software to identify trends and relationships between perceived value and purchase intention, with a focus on gender differences.